2020
DOI: 10.3390/polym12061283
|View full text |Cite
|
Sign up to set email alerts
|

Poly[oligo(ethylene glycol) methacrylate]-b-poly[(vinyl benzyl trimethylammonium chloride)] Based Multifunctional Hybrid Nanostructures Encapsulating Magnetic Nanoparticles and DNA

Abstract: We report on the preparation of novel and multifunctional hybrid spherical-shaped nanostructures involving a double-hydrophilic block copolymer, namely the neutral cationic poly[oligo(ethylene glycol) methacrylate]-b-poly[(vinyl benzyl trimethylammonium chloride)] (POEGMA-b-PVBTMAC) diblock copolymer, initially complexed with hydrophilic anionic magnetic nanoparticles (MNPs), and subsequently, with short deoxyribonucleic acid (113 bases DNA). The POEGMA-b-PVBTMAC copolymer, the copolymer/MNPs and the copolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Chroni et al . synthesized a magnetopolyplex incorporating a diblock copolymer, hydrophilic anionic magnetic nanoparticles, and short deoxyribonucleic acid ( 78 ). The intensity of this magnetopolyplex measured through dynamic light scattering was constant at low NaCl concentrations followed by a gradual decrease as ionic strength increased because a higher ionic strength produced a weaker interaction between DNA and carrier, reducing the amount of complexes.…”
Section: Effects Of Gene Vector Properties and Formulation Factors On In Vitro And In Vivo Performamentioning
confidence: 99%
“…Chroni et al . synthesized a magnetopolyplex incorporating a diblock copolymer, hydrophilic anionic magnetic nanoparticles, and short deoxyribonucleic acid ( 78 ). The intensity of this magnetopolyplex measured through dynamic light scattering was constant at low NaCl concentrations followed by a gradual decrease as ionic strength increased because a higher ionic strength produced a weaker interaction between DNA and carrier, reducing the amount of complexes.…”
Section: Effects Of Gene Vector Properties and Formulation Factors On In Vitro And In Vivo Performamentioning
confidence: 99%
“…2,[6][7][8][9][10][11][12] There are also other polymeric systems known for the preparation of polyplexes. [13][14][15][16][17] In the design of polyplexes, great emphasis is put on the ability of macromolecules to electrostatically bind and condense nucleic acids into nanometer sized particles. Many studies have shown that among others the polymer molar mass, topology, type of cationic functionality and charge density as well as polyplex surface charge and its conformation in the solution influenced the cytotoxicity and efficiency of transfection of such carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are being extensively developed and constructed due to their multi-functionality for the cure of various life-threatening diseases. A wide range of research has been reported to procure the effectiveness of such materials in theranostic applications [1][2][3][4][5][6][7][8][9]. Polymer nanomedicine is based on the development of copolymers that are biodegradable and biocompatible, and provides bioavailability and colloidal stability to the formed multifunctional hybrid nanomaterials and entrapped species.…”
Section: Introductionmentioning
confidence: 99%